Bird Strike-Induced Go-Around and Recorder Outage Leading to Gear-Up Landing and Runway Overrun: Case Study of Jeju Air Flight 7C2216 (HL8088) at Muan International Airport - Finda Ramadhani, Erdiana (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
Bird strikes remain a significant aviation hazard, particularly during critical flight phases such as approach, landing, and go-around. This study investigates the Jeju Air flight HL8088 accident on 29 December 2024 at Muan International Airport. The primary aim is to analyze the bird strike event and its consequences, contextualizing the accident within existing safety models. A qualitative case study approach was employed, utilizing accident reports, flight data reconstruction, and literature reviews on bird strike risks and their operational impacts. The findings reveal that the bird strike during the go-around severely damaged the aircraft, causing the landing gear to remain retracted and leading to a belly landing, runway overrun, and a post-crash fire that resulted in 179 fatalities. The accident underscores the heightened danger of bird strikes during take-off, landing, and go-arounds, as well as the compounded effects of secondary incidents. This case highlights the urgent need for improved bird strike management, more resilient aircraft design, and enhanced pilot training to mitigate future risks.